2021
DOI: 10.1097/prs.0000000000008633
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Race on Perioperative and Patient-Reported Outcomes following Autologous Breast Reconstruction

Abstract: Background: Racial disparities are evident in multiple aspects of the perioperative care of breast cancer patients, but data examining whether such differences translate to clinical and patient-reported outcomes are limited. This study examined the impact of race on perioperative outcomes in autologous breast reconstruction. Methods: A retrospective cohort study including all breast cancer patients who underwent immediate autologous breast reconstruction at a single institution from 2010 to 2017 was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Notably, secondary significant predictors of postoperative complications were also identified after microsurgical cases. These relationships have been upheld by previous studies, which have detected associations of microsurgery complications with demographic characteristics, 35 36 37 comorbidity history, 38 39 40 and perioperative variables. 41 42 43 These variables also had varying patterns of associations across different temporal periods; for example, BMI and race appeared to have a differential effect on complication depending on period, as White race and higher BMI protected against risk of complication in the first week but then significantly predicted higher risk in later periods.…”
Section: Discussionmentioning
confidence: 94%
“…Notably, secondary significant predictors of postoperative complications were also identified after microsurgical cases. These relationships have been upheld by previous studies, which have detected associations of microsurgery complications with demographic characteristics, 35 36 37 comorbidity history, 38 39 40 and perioperative variables. 41 42 43 These variables also had varying patterns of associations across different temporal periods; for example, BMI and race appeared to have a differential effect on complication depending on period, as White race and higher BMI protected against risk of complication in the first week but then significantly predicted higher risk in later periods.…”
Section: Discussionmentioning
confidence: 94%
“…When comparing patients who underwent reconstruction of the LE, African American race proved to be associated with higher risk of reoperation ( P = 0.05) when controlling for other potentially confounding risk factors. Recently, Oskar et al 31 found that African Americans patients had a higher incidence of 30-day major complications and were more likely to return to the operating room after autologous breast free flap reconstruction. Likewise, our group found that African American race was an independent risk factor for unplanned reoperation in patients undergoing head and neck free flap reconstruction 26 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Previous studies have demonstrated sociodemographic inequities in patient selection and surgical outcomes following ABR, dating back prior to the pandemic. [17][18][19][20][21] In conjunction with the aforementioned challenges presented by the global pandemic, it is critical to assess the effects that these challenges have had on ABR outcomes and whether the pandemic has exacerbated previous inequities or created new ones. To this end, our study aimed to assess whether the challenges imposed by the pandemic have led to differences in patient selection, hospital course and severity, and postoperative complications for patients who underwent ABR using the ACS-NSQIP, a nationally representative and validated database.…”
Section: Discussionmentioning
confidence: 99%